2023
DOI: 10.1371/journal.pone.0287519
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the capacity of vibrio fischeri to establish symbiosis with Euprymna scolopes

Aidan R. Donnelly,
Elizabeth J. Giacobe,
Rachel A. Cook
et al.

Abstract: Most animals establish long-term symbiotic associations with bacteria that are critical for normal host physiology. The symbiosis that forms between the Hawaiian squid Euprymna scolopes and the bioluminescent bacterium Vibrio fischeri serves as an important model system for investigating the molecular mechanisms that promote animal-bacterial symbioses. E. scolopes hatch from their eggs uncolonized, which has led to the development of squid-colonization assays that are based on introducing culture-grown V. fisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A 3.5-h exposure to a seawater inoculum of ES114 containing approximately 1,700 CFU/mL will result in half of hatchling population becoming bioluminescent by 24 h post-inoculation (p.i.) (Donnelly et al, 2023). However, we found that hatchlings exposed to inoculums of MRE010 exceeding 10 5 CFU/mL failed to emit bioluminescence (Figure 2).…”
Section: Mre010 Exhibits a Colonization Defectmentioning
confidence: 85%
“…A 3.5-h exposure to a seawater inoculum of ES114 containing approximately 1,700 CFU/mL will result in half of hatchling population becoming bioluminescent by 24 h post-inoculation (p.i.) (Donnelly et al, 2023). However, we found that hatchlings exposed to inoculums of MRE010 exceeding 10 5 CFU/mL failed to emit bioluminescence (Figure 2).…”
Section: Mre010 Exhibits a Colonization Defectmentioning
confidence: 85%